2013
DOI: 10.1371/journal.pbio.1001570
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Patterns of Increased Virulence in a Recently Emerged Wildlife Pathogen

Abstract: A bacterial pathogen of wild songbirds evolved higher virulence following its emergence in two separate regions of the host range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
138
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(148 citation statements)
references
References 75 publications
8
138
2
Order By: Relevance
“…gallisepticum virulence for house finches has previously been shown to increase over time in a given geographic region (18). Data presented here confirm previous findings in that a recent HFMG isolate, VA2013, continues to be highly virulent in house finches.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…gallisepticum virulence for house finches has previously been shown to increase over time in a given geographic region (18). Data presented here confirm previous findings in that a recent HFMG isolate, VA2013, continues to be highly virulent in house finches.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have shown that HFMG virulence evolution is not constant but is instead dynamic and dependent on ecological context (e.g., expanding versus established geographic ranges) (18,24). It is clear that M. gallisepticum was virulent for finches by the time that it was first noted and collected as VA1994 (coalescence analysis has indicated that HFMG first truly emerged in house finches 4 to 7 years prior [20,21]); however, here it is indicated that the period of time in which HFMG was circulating in finches prior to 1994 was insufficient to dramatically attenuate HFMG virulence for chickens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have contrasted virulence of a small number of isolates taken from different time periods, and from the eastern and western United States [25 -27]. These experiments suggest that parallel increases in virulence of the bacteria have occurred in both eastern and western North America over time, with the western increase following a lower initial virulence of the bacteria upon emergence on the Pacific coast [27]. These conclusions are valid to the extent that the small number of isolates used in these experiments [25 -27] are typical of the bacterial lineages circulating at the times and places where these isolates were collected.…”
Section: Resultsmentioning
confidence: 99%
“…This lineage has evolved rapidly, increasing in virulence, likely owing to selection on transmission [18]. In addition to this phenotypic change, exceptionally rapid genomic evolution has been documented in the bacterium [19].…”
Section: Human Impacts On Emerging Infectious Diseases Via Novel Specmentioning
confidence: 99%